Cauchy and his modern rivals. Issue 568 (March 2023) - Dunham, William
Abstract : In 1879, the Oxford mathematician Charles Dodgson (1832-1898) published Euclid and his modern rivals . This book compared the work of contemporary geometers to that of the Greek master from two millennia earlier. Dodgson, best known by his pen name of 'Lewis Carroll', much preferred Euclid. For him, the ancients outshone the moderns.